Students’ Competence In Using Singular And Plural Noun - Nurlaily Sofyan; Warti Kemhay; Fatimah M. Zen (English Education Department, Faculty of Education Muhammadiyah University of North Maluku, 2022)
Abstract: The researchers conducted this research to determine the extent of the students' competence in understanding singular and plural noun. The method used in this research was descriptive qualitative method which is tend to analyze data inductive. In this case, the researchers described the problems found as they are. Location of this research was SMP Al-Irsyad Kota Ternate, where the subjects of this study were the second grade students at SMP Al-Irsyad Kota Ternate with the number of students are 20 persons which consist of 10 males and 10 females. The instrument employed by the researchers was test. The researchers used multiple choice 20 numbers in order to know the students’ competence in using singular and plural noun. In this study, the researchers concluded that the ability of second grade students of SMP Al-Irsyad Kota Ternate in using singular and plural Noun is still very poor. Based on the results of the study, only 1 student who got the highest score of 55 with an average category from 19 students. Meanwhile, 19 students scored below 55 which is in the poor category. So, the average value of the percentage is 30.25%.